2018
DOI: 10.1002/path.5051
|View full text |Cite
|
Sign up to set email alerts
|

Prospective patient stratification into robust cancer‐cell intrinsic subtypes from colorectal cancer biopsies

Abstract: Colorectal cancer (CRC) biopsies underpin accurate diagnosis, but are also relevant for patient stratification in molecularly‐guided clinical trials. The consensus molecular subtypes (CMSs) and colorectal cancer intrinsic subtypes (CRISs) transcriptional signatures have potential clinical utility for improving prognostic/predictive patient assignment. However, their ability to provide robust classification, particularly in pretreatment biopsies from multiple regions or at different time points, remains unteste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 22 publications
2
50
0
Order By: Relevance
“…8,9 CRIS classifications offer a more robust measure of describing CRC molecular subtypes compared with CMS, as CRIS transcriptional profiles were developed independent of the tumour stromal content, which can be subject to sampling bias in CMS classifications. 21,22 We demonstrate for the first time that patients who are immune-cold (when defined by lowdensity CD3, CD4 and CD8 IHC expression) are most likely to associate with the poor prognosis of CRIS-B transcriptional profile, whilst no association with any particular CMS profile was identified. Patients with CRIS-B tumours are associated with aggressive disease and TGF-β signalling.…”
Section: Discussionmentioning
confidence: 80%
“…8,9 CRIS classifications offer a more robust measure of describing CRC molecular subtypes compared with CMS, as CRIS transcriptional profiles were developed independent of the tumour stromal content, which can be subject to sampling bias in CMS classifications. 21,22 We demonstrate for the first time that patients who are immune-cold (when defined by lowdensity CD3, CD4 and CD8 IHC expression) are most likely to associate with the poor prognosis of CRIS-B transcriptional profile, whilst no association with any particular CMS profile was identified. Patients with CRIS-B tumours are associated with aggressive disease and TGF-β signalling.…”
Section: Discussionmentioning
confidence: 80%
“…This issue was systematically analyzed, exploring the impact of the analysis of various regions of the tumor (central tumor, invasive from of the tumor, lymph node metastasis) on the gene expression analysis using the CSM and CRIS classification systems. The classification following the CMS system was tumor-region-dependent, while the CRIS classification was patient-specific and not affected by the region of the tumor analyzed [ 262 , 479 ]. To obviate the limitations of the CMS classification system for the classification of cancer cell lines, organoids and xenografts were derived from colorectal cancers and a CMS classifier (CMS scaller) optimized for preclinical models was developed [ 265 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research following the derivation of the CMS subtypes suggested that classification of a tumor into a single subtype may be inappropriate due to intratumoral heterogeneity [37][38][39][40] . Rather than classifying a tumor into a single subtype, it may be more accurate to measure the concentration of a particular cell type throughout a tumor.…”
Section: Discussionmentioning
confidence: 99%